In vivo analysis of centromeric proteins reveals a stem cell-specific asymmetry and an essential role in differentiated, non-proliferating cells - García del Arco, Ana; Edgar, Bruce; Erhardt, Sylvia (Cell reports, 2018)
Summary Stem cells of the Drosophila midgut (ISCs) are the only mitotically dividing cells of the epithelium and, therefore, presumably the only epithelial cells that require functional kinetochores for microtubule spindle attachment during mitosis. The histone variant CENP-A marks centromeric chromatin as the site of kinetochore formation and spindle attachment during mitotic chromosome segregation. Here, we show that centromeric proteins distribute asymmetrically during ISC division. Whereas newly synthesized CENP-A is enriched in differentiating progeny, CENP-C is undetectable in these cells. Remarkably, CENP-A persists in ISCs for weeks without being replaced, consistent with it being an epigenetic mark responsible for maintaining stem cell properties. Furthermore, CENP-A and its loading factor CAL1 were found to be essential for post-mitotic, differentiating cells; removal of any of these factors interferes with endoreduplication. Taken together, we propose two additional roles of CENP-A: to maintain stem cell-unique properties and to regulate post-mitotic cells.
Gesehen am 30.04.2018